The Splice Variant of the NCOR2 Gene BQ323636.1 Modulates ACSL4 Expression to Enhance Fatty Acid Metabolism and Support of Tumor Growth in Breast Cancer - Tsoi, Ho; You, Chan-Ping; Cheung, Koei Ho-Lam; Tse, Yin-Suen; Khoo, Ui-Soon (International journal of molecular sciences, 2025)
BQ323636.1 (BQ), a splice variant of NCOR2, is associated with endocrine therapy resistance and poorer prognosis in ER-positive breast cancer. This study investigates the role of BQ in modulating lipid metabolism to support tumor growth. RNA sequencing of BQ-overexpressing breast cancer cells revealed significant enrichment of fatty acid metabolism pathways (hsa01212 and hsa00061; p < 0.05), with ACSL4 identified as a key target. We show that BQ disrupts the NCOR2-PPARγ interaction, leading to ACSL4 upregulation, which enhances fatty acid oxidation (FAO), acetyl-CoA by 1.8-fold, and ATP production by 2.5-fold to fuel tumor proliferation. BQ also upregulates FASN and SCD, increasing lipids. A metabolites study with mass spectrometry indicated that BQ overexpression increases the fatty acid amount from 47.97 nmol/106 cells to 75.18 nmol/106 cells in MCF7 and from 56.19 nmol/106 cells to 95.37 nmol/106 cells in ZR-75. BQ activates NRF2, which mitigates ROS-induced stress, promoting cell survival. Targeting ACSL4 with the inhibitor PRGL493 reduced ATP production and suppressed tumor growth in vitro and in vivo, without inducing apoptosis, suggesting a cytostatic effect. PRGL493 treatment can reduce BQ overexpressing tumors by 40% in the xenograft model. These results highlight BQ can serve as a transcriptional hub driving lipid metabolism via ACSL4 in breast cancer. Our findings suggest that ACSL4 inhibition could be a novel therapeutic strategy to overcome treatment resistance in high-BQ expressing ER-positive breast cancer.